Artificial intelligence in the food industry - Nikolola-Alexieva Valentina; Valeva Katina; Pashev Stoyan (BIO Web of Conferences, 2024)
The growth of the planet’s population requires the application of innovative technological solutions for its nutrition. Artificial intelligence, as part of the technological toolkit of Industry 4.0, having a strong transforming effect in modern society, is perceived as a strategic factor for increasing productivity, efficiency and innovation in a number of sectors, including the food industry. The global food and beverage artificial intelligence market in 2021 is valued at USD 4.49 billion. It is expected to grow at a CAGR (average annual rate) of 45.4% to reach US$ 83.4 billion by 2029. The main goal of every industrial enterprise in the food industry is to produce high-quality products at the lowest possible cost. The application of AI can contribute to maintaining a higher quality of the manufactured product, through rapid quality control and visualization of the result. AI can aggregate and analyze data in real-time making recommendations to improve operational activities, can analyze data, uncover trends and recommend actions to increase efficiency. The result of the implementation of artificial intelligence in the food industry contributes to driving the growth of the market.